Question
Asked Oct 29, 2019
8 views

If f'(1) = 1, f(2) = 3, f'(2) = -3, f'(4) = 10, g(1)= 4, g'(1) = 2, find (f o g)'(1) and (f(xg(x)))' at x=1.

check_circle

Expert Answer

Step 1

Apply chain rule on to find (fog)'(1)

then plug the given values. 

Answer: (fog)'(1) = 20

help_outline

Image Transcriptionclose

(fog)(1) f(g(1) =f'(g(1))g'(1 =f'(4)(2) 10(2) 20

fullscreen
Step 2

Apply chain rule. Then use pr...

help_outline

Image Transcriptionclose

(f(xg(x)) =f'(xg(x)[xg(x)] =f'(xg(x))[1xg(x)+xg'(x)] =f'(xg(x))[g(x)+xg'(x)]

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Other